LOW COST AIRLINES IN SOUTH EAST ASIA: A VIEW FROM SINGAPORE - Henderson, Joan C (ASEAN Journal on Hospitality and Tourism, 2006)
The paper is concerned with the concept and characteristics of low cost airlines which are a well established sector in North American and European civil aviation industries, but a fairly recent phenomenon in South East Asia. Trends within the region are discussed with particular reference to the case of Singapore which has seen an expansion in low cost airline activity. Further growth seems possible and likely, although new entrants are shown to face both opportunities and problems. The Western business model appears to be applicable in a regional context, yet some modifications may be necessary to suit the different conditions in the market and those prevailing more widely.